2012
DOI: 10.1002/cncr.27633
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous endoscopic gastrostomy in oropharyngeal cancer patients treated with intensity‐modulated radiotherapy with concurrent chemotherapy

Abstract: BACKGROUND The clinical benefit of routine placement of prophylactic percutaneous endoscopic gastrostomy (pPEG) tubes was assessed in patients with oropharyngeal cancer (OPC) who are undergoing intensity-modulated radiotherapy (IMRT) with concurrent chemotherapy. METHODS From 1998 through 2009, 400 consecutive patients with OPC who underwent chemoradiation were included. Of these, 325 had a pPEG and 75 did not (nPEG). Weight and albumin change from baseline to mid-IMRT, end of IMRT, 1 month post-IMRT, and 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
61
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 22 publications
7
61
0
2
Order By: Relevance
“…We also demonstrate little harm in postponing PEG tube placement in this patient population. The median time to PEG tube removal was 3.3 months, which is consistent with a recent large study 5 in a similar patient population who underwent concurrent chemotherapy and intensity-modulated radiation therapy with prophylactic PEG tubes placed. In addition, by 1 and 3 months following CRT, no difference was observed in percentage median weight loss between those who required a PEG tube in our study and those who did not.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…We also demonstrate little harm in postponing PEG tube placement in this patient population. The median time to PEG tube removal was 3.3 months, which is consistent with a recent large study 5 in a similar patient population who underwent concurrent chemotherapy and intensity-modulated radiation therapy with prophylactic PEG tubes placed. In addition, by 1 and 3 months following CRT, no difference was observed in percentage median weight loss between those who required a PEG tube in our study and those who did not.…”
Section: Discussionsupporting
confidence: 76%
“…The placement of prophylactic PEG tubes has been reported in several recent retrospective series as a safe and effective method for preventing nutritional decline during treatment for head and neck cancer. [1][2][3][4][5] However, the placement of a prophylactic PEG tube carries measurable risks, most notably an infection rate of 5% to 8%, along with diarrhea, constipation, electrolyte abnormalities, gastrointestinal bleeding, a clogged lumen and tube replacement, and metastatic seeding at the gastrostomy site. [4][5][6][7] In addition, some groups have suggested that avoidance of PEG tube placement during therapy may be associated with a lower risk of long-term dysphagia outcomes such as PEG tube dependence or pharyngoesophageal stricture.…”
mentioning
confidence: 99%
“…Two of the 20 studies were randomized controlled trials (RCTs) [71,72] (see Table 1), one followed a case-control design [83], and the remaining 17 involved observational cohorts (three prospective [84][85][86], nine retrospective [22,44,67,[87][88][89][90][91][92], three mixed (with some outcomes being retrieved retrospectively and others being collected prospectively) [46,93,94], and two unclear [50,95]). …”
Section: Study Characteristicsmentioning
confidence: 99%
“…Because the aspiration rates ranged from %36 to %81 in the published studies which was higher than our rate (19)(20)(21)(22). The strongest part of our study and Patterson's study about showing the actual aspiration rate may be that patients who reported normal swallowing were not excluded from the study (18). While the aspiration severity was gradually increased by the time, there is also a gradual decrease in weight of the patients.…”
Section: Discussionmentioning
confidence: 38%